Analysis of anchor drop and drag over the pipeline - Lai, Kah Yip (2009)
The present work examines the denting response of a pipeline subjected to quasi-static anchor loading, imposed by a triangular block with patch profile. Using Simulation module of ANSYS Workbench V11.0, a parametric study is conducted and denting force-displacement results are obtained for various pipe’s thickness, lengths, internal pressures, indenter widths and orientations.